State Responsibility and the Environmental Protection Crisis from a Legal Philosophy Perspective: Tanggung Jawab Negara dan Krisis Perlindungan Lingkungan Hidup dalam Perspektif Filsafat Hukum - Winata, Elisa; Nelson, Nelson; Zidane, Arqily Rafif; Harahap, Odi Alfazen; Ambarita, Dicki Candra (Academia Open, 2026)
General Background Environmental protection constitutes a fundamental obligation of the state encompassing constitutional, moral, and philosophical dimensions, particularly in safeguarding human rights to a good and healthy environment. Specific Background In Indonesia, environmental governance is formally supported by comprehensive legal frameworks; however, recurring environmental degradation indicates persistent challenges in implementation. Knowledge Gap There remains a critical gap between established legal norms and their practical enforcement, reflected in normative failure and law enforcement dysfunction. Aims This study aims to analyze the concept of state responsibility in environmental protection from a legal philosophy perspective and to examine the causes of normative failure and enforcement dysfunction in Indonesia. Results The findings reveal that state responsibility extends beyond formal rule-making to ensuring ecological justice, sustainability, and intergenerational protection, yet is undermined by regulatory disharmony, vague provisions, legal loopholes, and reactive, inconsistent enforcement practices, as illustrated by the tin commodity governance case. Novelty This study integrates legal philosophy with normative legal analysis to demonstrate that environmental protection failures stem from systemic weaknesses in legal substance, policy coherence, and enforcement structures. Implications The study underscores the necessity of regulatory harmonization, sustainability-oriented policymaking, and strengthened enforcement mechanisms to ensure effective, just, and sustainable environmental protection. Highlights: State obligations include ecological justice and intergenerational sustainability beyond formal regulation. Legal system weaknesses arise from regulatory inconsistency, unclear provisions, and structural loopholes. Enforcement practices remain reactive and selective, limiting prevention of environmental violations. Keywords: State Responsibility, Environmental Protection, Legal Philosophy, Normative Failure, Law Enforcement.